Olivia and the school carnival - Gallo, Tina.; Wolek, Guy; Nickelodeon (Television network) (New York : Simon Spotlight, 2010)
Olivia works hard to create a wonderful carnival for Parents Night.
"Based on the screenplay 'Olivia Runs a Carnival' written by Joe Purdy."
"Based on the TV series Olivia as seen on Nickelodeon"--T.p. verso.
2.8
K-3.
K-3
Keywords: Carnivals -- Juvenile fiction; Olivia (Fictitious character : Falconer) -- Juvenile fiction; Schools -- Juvenile fiction; Carnivals -- Fiction; Olivia (Fictitious character : Falconer) -- Fiction; Schools -- Fiction; Carnivals -- Fiction; Olivia (Fictional character : Falconer) -- Fiction; Radio and television novels; School stories; Picture books for children; Radio and television novels